Neuroimmunology of Sleep - Pandi-Perumal, S. R.; Pandi-Perumal, S. R.; Cardinali, Daniel P.; Cardinali, Daniel P.; Chrousos, Georgios.; Chrousos, Georgios. (Springer US : Imprint: Springer, 2007)
During the last few decades, sleep medicine and science, and many of their diverse aspects, have emerged as areas of intense medical and scientific interest. Of these, sleep and neuroimmunology, which cut across many behavioral states, are highly interlinked, inherently fascinating and touching upon many facets of human health and well-being. Elucidating the roles of immune substances and cells in central nervous system functions, especially their involvement in the regulation of sleep and wakefulness, may help unravel pathophysiologic mechanisms of sleep disorders and improve their management. Neuroimmunology of Sleep provides an introduction to the interphase between sleep and neuroimmunology. Written both from basic and clinical perspectives, the volume contains useful information to many biomedical professionals and students of human biology. This informative and forward-looking volume will be valuable to sleep researchers, neuroimmunologists, psychiatrists, psychologists, neurologists, and all physicians or health-care professionals who evaluate and treat patients with sleep problems. In addition, this volume will be helpful to medical students and clinicians of various disciplines who want to get an overall grasp of the neuroimmunology of sleep field. S.R. Pandi-perumal, MSc., Comprehensive Center for Sleep Medicine, Department of Pulmonary, Critical Care, and Sleep Medicine, Mount Sinai School of Medicine, New York, NY 10029, U.S.A. D.P. Cardinali, MD., PhD., Department of Physiology, Faculty of Medicine, University of Buenos Aires, Paraguay 2155, 1121, Buenos Aires, Argentina. G.P. Chrousos, MD, FAAP, MACP, MACE, First Department of Pediatrics, Athens University Medical School, Aghia Sophia Children's Hospital, 115 27 Athens, Greece and Reproductive Biology and Medicine Branch, National Institute of Child and Human Development (NICHD), Bethesda, MD, USA.